2011
DOI: 10.1364/oe.19.006699
|View full text |Cite
|
Sign up to set email alerts
|

Additional effective medium parameters for composite materials (excess surface currents)

Abstract: Modified boundary conditions for composite material are suggested. The modified RT-retrieval procedure yields bulk values of effective impedance and refractive index, which are independent of system size and boundary realization, whereas the conductivities of the excess surface currents depend on the property of the interface. Simultaneous treatment of all the possible realizations of the system removes the dependence. The accuracy of the latter procedure is the same as the usage of static effective parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…We note that the resonant appearance of permeability retrieved from the scattering parameters can occur due to numerous factors, including the effects of spatial dispersion, 37,38 which are not relevant in our case, as well as the effects of the finite size of the sample, which imposes Fabry-Perot resonance (half-wavelength) or leads to remarkable boundary effects. [39][40][41] In our case, the anti-resonance of metamaterial composed of the 4 layers is observed and can be explained by the presence of Fabry-Perot resonance. Such resonances can be corrected by the refined retrival techniques.…”
supporting
confidence: 52%
“…We note that the resonant appearance of permeability retrieved from the scattering parameters can occur due to numerous factors, including the effects of spatial dispersion, 37,38 which are not relevant in our case, as well as the effects of the finite size of the sample, which imposes Fabry-Perot resonance (half-wavelength) or leads to remarkable boundary effects. [39][40][41] In our case, the anti-resonance of metamaterial composed of the 4 layers is observed and can be explained by the presence of Fabry-Perot resonance. Such resonances can be corrected by the refined retrival techniques.…”
supporting
confidence: 52%
“…For bounded layered systems the key moment of the problems is the boundary conditions. Modification of the boundary conditions by introduction of additional surface currents suggested in [75] returns the conventional permittivity and permeability of metamaterials their usual physical properties. The modified retrieval procedure based on reflection/transmission yields bulk values of effective impedance and refractive index, which are independent of system size and boundary realization, whereas the conductivities of the excess surface currents depend on the property of the interface [75].…”
Section: Beyond the Effective Medium Theory: Nonlocality Corrections mentioning
confidence: 99%
“…Although this process is valid for lattice periods of MMs much smaller than resonance wavelength, near field effects in the boundaries of MM slabs due to spatial dispersion are generally not considered in this determination. In recent studies [6], [7], it is demonstrated that in addition to the approaches of transition layers [8] and additional bulk parameter [9], such effects can equivalently be analyzed by the concept of additional surface currents. This concept has been taken into consideration on accurate determination of electromagnetic parameters of isotropic MMs [6], [10], [11], where it is demonstrated that around the resonance region, semi-infinite reflection Manuscript coefficient at air-MM boundary is no longer equal to the negative of the reflection coefficient at MM-air boundary.…”
Section: Introductionmentioning
confidence: 99%